Halagahan mga teksto ng pagturing - Flores, Patrick D.; Ateneo de Naga University Press (Naga City Ateneo de Naga University Press, 2021)
Criticism on Philippine film and motion picture industry in the Philippines.
Keywords: Film criticism -- Philippines; Motion picture industry -- Philippines; Motion pictures -- Social aspects -- Philippines; Motion pictures -- Philippines -- History